The Influence of Customer Relationship Management on Cross-Selling and Upselling Strategies in Marketing - Nath, Soma (International Journal of Engineering and Management Research, 2020)
In this research paper, we integrating CRM into upselling and cross-selling tactics increases short-term revenue and fosters long-term loyalty. Businesses can attain greater client retention and long-term growth by effectively combining personalization, employee training, and channel selection. CRM should not be viewed as a simple technological instrument, but rather as a comprehensive strategic strategy.